COMPARATIVE STUDY OF SINGLE STEEL PILE BEARING CAPACITY BETWEEN GEO5 SOFTWARE AND EMPIRICAL FORMULA METHOD - Dwi Imam Riva'i; Yudhi Lastiasih; Trihanyndio Rendy Satrya (Journal of Civil Engineering, 2022)
Abstract: Pile foundation is a part of the Sub-structure that is used to receive and distribute loads from the superstructure to the ground at a certain depth, where it requires suitable bearing capacity. Empirical formula is the one of the methods for calculating pile bearing capacity that based on Standard Penetration Test (SPT) value. This method consumes plenty of time compared with the current method using Geo 5 software. However, the pile bearing capacity results among these methods should be verified beforehand. Therefore, it is necessary to do a comparison of pile bearing capacity laid on various soil types between the empirical formula and the Geo5 program based on SPT data to obtain the value of the correction factor and to find out which method is nearest to the Geo5 software. The Luciano decourt empirical method results are closer to the Geo5 software for all soil types, both of the end bearing and floating pile conditions with ratio values of 0.90 and 1.09 for dominant clay, 0.97 and 0.96 for dominant silt, and 0.84 and 0.89 for dominant sand. As for the Bazaara Empirical Method, the results are closer to the Geo5 program for the dominant group of sand in floating pile conditions with a ratio value of 0.99. Hence, the Luciano Decourt's empirical formula is more recommended than Bazaara's empirical formula.